The effects of urban agricultural areas on the intensity of atmospheric heat islands in Florianopolis- SC - Pereira da Silva, Gustavo Henrique [UNESP]; Costa Trindade Amorim, Margarete Cristiane de [UNESP] (Univ Federal Roraima, 2022)
This paper aimed to analyze the effects of urban agricultural areas on the intensity of the heat islands in Florianopolis -SC. The methodological procedures consisted of data collection in 12 fixed points distributed in 3 urban agricultural areas, 8 in intraurban areas and 1 in an area without the presence of construction materials, in February 2019. The results revealed the spatial and temporal variation of air temperature intensity, associated with the uses and occupation of the surrounding land and the different atmospheric systems operating in the month of study. During daytime (9 am, 3 pm), the highest air temperature intensities were detected, in which the points located to the South from the island of Santa Catarina (points 1, 2, 3 and 4), including those of urban agriculture (points 1 and 2), with vegetation cover, were hotter than the others. During nighttime, the intensities of the temperatures decreased, with emphasis on the agricultural areas studied, which in many days became islands of freshness, what demonstrates the importance of this type of land use in reducing temperatures in an urban environment.
Keywords: Urban and periurban agriculture; Heat islands; Urban climate; Florianopolis-SC